Standards of coherence in second language reading: Sentence connectivity and reading proficiency - Nahatame, Shingo (Reading in a foreign language, 2017)
Standards of coherence are one of the major factors that influence reading comprehension. This study investigated the standards of coherence that second language (L2) learners employ when reading. In a pair of experiments, Japanese learners of English read two-sentence texts with varying causal and semantic relatedness between sentences and then judged the coherence of the texts on a 5-point scale. Analysis of the judgment ratings indicated that both causal and semantic relatedness affected readers’ perceived text coherence. The texts high in causal or semantic relatedness were judged as more coherent. Furthermore, when making judgments, lower proficiency readers were likely to place greater emphasis on semantic relatedness, whereas higher proficiency readers were likely to place greater emphasis on causal relatedness. These results suggest that L2 readers generally base standards of coherence on causal and semantic relatedness between sentences; however, readers of varying L2 skill levels may adopt different standards of coherence.